2001
DOI: 10.1097/00129804-200109000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally Inserted Central Catheters in Children With Cystic Fibrosis

Abstract: Peripherally inserted central catheters (PICCs) are widely used in the management of cystic fibrosis (CF) in children and adults. The authors present a collection of eight case reports of patients with CF in whom removal of PICCs was difficult, including two PICCs that required surgical removal. The cases were observed in a regional pediatric CF unit in the United Kingdom. Possible etiology and strategies that can be used to achieve catheter removal are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
9
0
2
Order By: Relevance
“…In CF patients difficulties regarding PICC removal have also been described [32]. Continuous traction or moderately strong pulling maneuvers were successful in dislodging the catheters in most of cases in which they were performed [32,33]. In our series, the site of insertion was carefully cleaned in order to remove coagulated blood, and the short duration of 14 days was probably insufficient for tethering.…”
Section: Author (Ref)mentioning
confidence: 61%
See 1 more Smart Citation
“…In CF patients difficulties regarding PICC removal have also been described [32]. Continuous traction or moderately strong pulling maneuvers were successful in dislodging the catheters in most of cases in which they were performed [32,33]. In our series, the site of insertion was carefully cleaned in order to remove coagulated blood, and the short duration of 14 days was probably insufficient for tethering.…”
Section: Author (Ref)mentioning
confidence: 61%
“…In most cases there were associated factors such as bacteraemia and a long duration of catheterization [30,31]. In CF patients difficulties regarding PICC removal have also been described [32]. Continuous traction or moderately strong pulling maneuvers were successful in dislodging the catheters in most of cases in which they were performed [32,33].…”
Section: Author (Ref)mentioning
confidence: 99%
“…Vasodilatation with a topical glycery trinitrate patch proximal to the insertion site has also been used for difficult PICC removal[ 11 ]. While Nitroglycerin can dilate vascular, the Nitroglycerin Ointment is contraindicated in children younger than 18-years-old.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach is used for removal as a final method. In their study, Miall et al [ 11 ] reported that among 8 patients with pancreatic cystic fibrosis who had difficulty in extubation of PICC catheters, 2 underwent successful surgical removal. Nonetheless, in the present case, considering the child's condition, it was questionable whether the child could tolerate surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation